Analisis Indeks Kekeringan Lahan Gambut Menggunakan Data Hujan TRMM Di Kabupaten Siak - Ade Mustika Martin; Sigit Sutikno; Siswanto Siswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A drought occurs when there is a lack of precipitation over an extended period of time, usually a season or more, resulting in a water shortage. BNPB, National Disaster Mitigation Regency has issued a drought disaster risk index map in Riau province which has a moderate and high level of drought risk. Siak regency is one that is experiencing the risk of drought in riau province. Therefore, drought index analysis using rainfall data from TRMM satellite (Tropical Rainfall Measuring Mission) was analyzed using Standardized Precipitation Index (SPI) method. Drought deployment and hotspot calculations in maps in GIS (Geographic Information System). A half month period on grid 5 with a value of (-4.589) and a month on grid 4 with value (-3,863) in February 2014 is the most severe dry category SPI classification. The association of fires affected by the meteorological drought index affected the a half month period due to the presence of more fires. However, not only the meteorological drought index affects fires, but can be caused by soil types, land cover and over land conversion.Keywords: drought, drought index, SPI, TRMM, GIS